The Influence of Powder Reuse on the Properties of Laser Powder Bed‐Fused Stainless Steel 316L: A Review. Issue 9 (9th July 2022) - Douglas, Rory; Lancaster, Robert; Jones, Thomas; Barnard, Nicholas; Adams, Jack
Abstract : There is a clear economic benefit for the recycling of metallic powder during additive manufacturing (AM). Laser powder bed fusion (L‐PBF) is one such AM process and research has found that the properties of the powder feedstock can change when the powder is reused through mechanisms such as spatter generation and alterations in chemistry. Such changes to powder properties can accumulate and may lead to significant differences in the mechanical properties of the final component. Often the changes to part properties are reasonably small; however, there is not currently enough understanding of the specific links between powder properties and the characteristics of the end component for the effects of powder recycling to be discounted. Herein, the typical lifecycle of stainless steel 316L powder in L‐PBF, the changes that occur to the powder feedstock, and the effects that this may have on the mechanical properties of components manufactured with recycled powder are reviewed. Abstract : This paper reviews the typical lifecycle of stainless steel 316L powder in the additive manufacturing process laser powder bed fusion, the changes that occur to the powder feedstock, and the effects that this may have on the mechanical properties of components manufactured with recycled powder.